Metaphorical Analysis of Teachers’ and Students’ Perceptions of ESP - Cita Nuary Ishak (Language Center of Islamic Institute of Uluwiyah (IAI Uluwiyah) Mojokerto Indonesia, 2019)
Despite the growing interest in English for Specific Purposes, little is known about university teachers’ and students’ perceptions towards the subject. The present research aims to investigate teachers’ and students’ perceptions towards ESP teaching and learning process in an Indonesian university. Employing metaphorical analysis, fifty students’ metaphors and thirty teachers’ metaphors were collected. The analysis of the metaphors revealed that while most students have neutral attitude towards ESP, most teachers experience ambivalences when teaching ESP. The study also found that the teachers conceptualized ESP as a physical activity requiring process, careful measurement, effort, preparation, and time.